Faktor – faktor yang Mempengaruhi Rendahnya Cakupan Kunjungan Nifas (KF3) di Puskesmas Hamparan Perak Kecamatan Hamparan Perak Kabupaten Deli Serdang Tahun 2024 - Dessy Ratna Sari; Minta Punguan Simbolon; Debby Chyntia Yun; Ariska Fauziyanti; Ninsah Mandala Putri Sembiring (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2024)
Background: Postpartum care is needed in the period after delivery to detect early problems or treat postpartum illnesses. More than 65% of maternal deaths occur during the first 42 days postpartum. This study aims to analyze the factors that influence postpartum visits in Indonesia. Method: The research uses quantitative research in the form of an analytical survey with a cross sectional design. Units. Results: Based on the results of logistic regression, predisposing factors that have the opportunity to influence complete postpartum visits are maternal age 20-35 years (OR 0.885), higher education (OR 1.167), parity ? 2 (OR 1.090), delivery by cesarean/vacuum/ forceps, etc. (OR 1.491), delivery in a health facility (OR 1.489), complete pregnancy check-up (OR 1.613), and regional Sumatra (OR 0.510). Enabling factors that have the opportunity to influence postpartum visits are unemployed status (OR 0.954) and having health insurance (OR 1.141). The need factor that has the opportunity to influence postpartum visits is having a history of pregnancy complications (OR 0.948). Conclusion: Factors that influence postpartum visits are maternal age, education, parity, method of delivery, place of delivery, prenatal check-up, regional residence, employment status, ownership of health insurance, and history of pregnancy complications.